2015
DOI: 10.5603/fm.2015.0018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, imaging and genetic analysis of double bilateral radix entomolaris

Abstract: (Folia Morphol 2015; 74, 1: 127-132)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…2A). Our results are in line with previous studies on Asian populations (5)(6)(7)(8)(9)(10)(11)(12)34), especially the Taiwanese (5)(6)(7)(8)(10)(11)(12), suggesting that a DLRs is considered to be a normal morphologic variant and can be seen as an Asiatic trait (31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2A). Our results are in line with previous studies on Asian populations (5)(6)(7)(8)(9)(10)(11)(12)34), especially the Taiwanese (5)(6)(7)(8)(10)(11)(12), suggesting that a DLRs is considered to be a normal morphologic variant and can be seen as an Asiatic trait (31).…”
Section: Discussionsupporting
confidence: 93%
“…DLR typically refers to the presence of an additional root existing lingually to a distal root and is a major anatomic variant in PMFMs (5)(6)(7)(8)(9)(10)(11)(12). This morphologic characteristic has been recognized as a genetically determined racial trait (31). Considerable heterogeneity of DLR frequency has been described in previous studies (5)(6)(7)(8)(9)(10)32).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that the presence of this dental trait has been thought to be a genetically determined racial trait. In whites and blacks, the frequency of DLR is less than 5%, while in populations with ethnic Mongolian characteristics (for example, Chinese, Japanese, Korean, and Taiwanese), the frequency of DLR ranges from 5 to 30% [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…knowledge of this variation by clinician increases success rate therefore, every clinician should be familiar with abnormal variation and its prevalence among population. Distolingual root or radix entomolaries RE Considered as one of the most common genetic racial trait in mandibular molars (14) . Digital perapical radiographs have been chosen for the current study as-they are regularly used as a base for collecting diagnostic information (15) .…”
Section: Discussionmentioning
confidence: 99%